2019
DOI: 10.1017/cem.2019.106
|View full text |Cite
|
Sign up to set email alerts
|

LO63: Humanoid robot-based distraction to reduce pain and distress during venipuncture in the pediatric emergency department: A randomized controlled trial

Abstract: Introduction: Intravenous insertion (IVI) is identified by children as extremely painful and the resultant distress can have lasting negative consequences. There is an urgent need to effectively manage such procedures. Our primary objective was to compare the pain and distress of IVI with the addition of humanoid robot-based distraction to standard care, versus standard care alone. Methods: This two-armed randomized controlled trial (RCT) was conducted from April 2017 to May 2018 at the Stollery Children's Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Within pediatrics, SARs have been increasingly implemented to ameliorate pain and distress, with positive outcomes [7,1013]. Specifically, robots have been shown to reduce distress for needle-related procedures in the pediatric emergency department (ED) [7]. Similar results exist for pre-procedure and vaccination-related pain and distress [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within pediatrics, SARs have been increasingly implemented to ameliorate pain and distress, with positive outcomes [7,1013]. Specifically, robots have been shown to reduce distress for needle-related procedures in the pediatric emergency department (ED) [7]. Similar results exist for pre-procedure and vaccination-related pain and distress [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Socially assistive robotics (SARs) have the potential to be uniquely beneficial as a novel technology with potential to create a more immersive experience for children than other known digital distraction modalities. Several recent studies have shown promising results regarding the application of SAR to mitigate children's procedure-related pain and distress [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the guiding principles for using books, bubbles, pinwheels, games, and videos have been seated within a framework that "distraction" was the primary mechanism of action. Previous studies have used the socially assistive robot NAO (Aldebaran Robotics ® ) to distract children and reduce pain during vaccination [10] and more recently during IV placement where early study results also showed no change in FACES pain scale but improvement in distress by the Observational Scale of Behavioural Distress-Revised (OSBD-R) [24]. Our study differs significantly from this work because the empathic IVEY is not acting as simple distraction.…”
Section: Discussionmentioning
confidence: 56%
“…The system will be tested in the target environment throughout the project period, culminating in a two-site randomised clinical trial at the end of the project. The target robot platform is the Nao robot from SoftBank Robotics (Figure 1), which has been widely used in child-robot interaction studies, including several in the identical clinical context we are targeting [2,12]. Concretely, this project is addressing the following research questions: To explore these questions we are employing a range of interdisciplinary techniques: the robot behaviours will be defined and developed through a co-design approach that includes children, family members, and healthcare providers; the robot software will be implemented using state-of-the-art AI techniques, and will be evaluated using approaches from usability testing; the clinical trial will be carried out using standard tools and techniques; while the investigation of ethical and social implications will rely on techniques from content analysis.…”
Section: Overview Of This Projectmentioning
confidence: 99%
“…Recently, several studies have explored the use of social robots in this context, specifically providing psychological interventions during needle-based procedures [2,12,27]. The results of these studies have generally been positive, showing high acceptance among the target population as well as promising initial clinical results.…”
Section: Introductionmentioning
confidence: 99%